Effect of foliar spraying with humic acid and seaweed extract on growth and yield of pepper (Capsicum annum L.) - dakar, fatima (Submission and Review of Research -Biological Sciences Series, 2025)
The research was conducted in Jowab Yashout village (Jableh/Lattakia) during 2024. The research aimed to study the effect of foliar spraying with humic acid and seaweed extract on the growth and productivity of pepper plants Capsicum annum L. Two cultivars of pepper plants (Qorn al-Ghazal / aljraseah), the experement included six treatments: control that plants were sprayed with water only T1, plants sprayed with humic acid 1ml/L T2, plants sprayed with humic acid 2 ml/L T3, plants sprayed with seaweed extract 1 ml/L T4, plants sprayed with seaweed extract 2 ml/L T5, and humic acid 1 ml/L with seaweed extract at concentration of 1 ml/L T6). Results showed a significant superiority of the foliar spray treatment with humic acid and seaweed extract in all studied traits over the rest of the treatments in both cultivars. Where, they reached (101.26 cm plant height – 282.9 leaf/plant number of leaf -14862 cm2 leaf surface area - 82.23 flowers/plant number of flowers per plant– 47.53 fruits/plant number of fruits per plant – 1.76 kg/plant productivity per plant) in the Qorn al-Ghazal cultivar, while they reached (87.53 cm plant height– 217.4 leaf/plant number of leaf- 18220 cm2 leaf surface area– 79.5 flowers/plant number of flowers per plant– 24.57 fruits/plant number of fruits per plant– 2.94 kg/plant productivity per plant ) in the Aljraseah pepper cultivar.